Harmful impacts of microplastic pollution on poultry and biodegradation techniques using microorganisms for consumer health protection: A review - Mohamed E. Abd El-Hack; Elwy A. Ashour; Fatemah AlMalki; Asmaa F. Khafaga; Mahmoud Moustafa; Mohammed O. Alshaharni; Islam M. Youssef; Ahmed A. Elolimy; Sylwester Świątkiewicz (Poultry Science)
Microplastics (MPs) are small plastic particles less than five millimeters in size. Microplastic pollution poses a serious threat to ecosystems, affecting both biotic and abiotic components. Current techniques used to eliminate microplastics include recycling, landfilling, incineration, and biodegradation. Microplastics have been detected in various animal species, including poultry, fish, mammals, and invertebrates, indicating widespread exposure and potential bioaccumulation. In the Middle East, MPs contamination was discovered in chicken purchased from food shops, chain supermarkets, and open markets. The contamination levels ranged from 0.03±0.04 to 1.19±0.72 particles per gram of chicken meat. In poultry, microplastics negatively affect production and harm vital organs such as the kidneys, spleen, and lungs. In humans, exposure to microplastics can lead to inflammation, immune responses, metabolic disturbances, DNA damage, neurological damage, and even cancer upon contact with mucosal membranes or absorption into the body. Several studies have explored the use of microorganisms, including bacteria, fungi, and algae, to degrade microplastics, offering an economical and environmentally friendly solution. Different polymers were cultured with strains of Bacillus spp. (SB-14 and SC-9) and Streptococcus spp. (SC-56) for a duration of 40 days. Degradation rates for LDPE were 11.8 %, 4.8 %, and 9.8 %. The rates of deterioration for HDPE were 11.7 %, 3.8 %, and 13.7 %. Rates for polyester beads were 17.3 %, 9.4 %, and 5.8 %. This review focuses on the effects of microorganisms in removing microplastic pollution, the detrimental impact of microplastics on poultry production, and the connection between microplastic pollution and human health.